The Early Marriage in Kaliboto Kidul on Maqasid Sharia Perspective - Sarkowi, Sarkowi; Qosyim, Roshiful Aqli (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2023)
The practice of early marriage breeds many problems. This case also quite a lot happened in Kaliboto Kidul, Lumajang. This study traces why the phenomenon occurs. The article also looks at the practice with the perspective of maqashid sharia. Therefore, the important debate is whether the practice of early marriage is entirely problematic or on the other hand has benefits. This paper is packed with an interdisciplinary approach; normative, sociological, and philosophical. This article found that the main reason for the practice of early marriage is because of pregnancy out of wedlock, among other reasons. For this reason, in the perspective of Maqasid Shari'ah, the practice of early marriage can be the best choice to protect women and children (hifz an-nafs and an-nasl), although it still gives birth to new effects, namely during childbirth. However, the danger is still assessed at a lower level of dharuri than allowing the child to be trapped in adultery. Therefore, this article confirms that in the normative, sociological, and philosophical context the practice of early marriage does not fully present harm, but it becomes an option to protect other potential harms.